Policy and Technological Synergies in Smart City Transportation - Wahyuilahi, Muhammad; Setiadi (Sinergi International Journal of Logistics, 2025)
This study investigates the integration of advanced technologies, such as big data, machine learning, and the Internet of Things (IoT), within intelligent transportation systems (ITS) in smart cities. The purpose is to identify the key factors influencing the successful implementation of ITS, focusing on technological, policy, and socio-cultural dynamics. A narrative review methodology was employed, synthesizing findings from multiple studies across various regions. The results reveal that while technological advancements have improved urban mobility, the success of ITS depends on the alignment of policies, infrastructure, and public perception. Key barriers include bureaucratic inertia, fragmented governance, and regulatory inflexibility. The study suggests that adaptive regulatory frameworks, enhanced public-private partnerships, and community involvement are essential for overcoming these challenges. Future research should focus on integrating socio-political factors with technological development to create more holistic solutions. The findings underline the need for a multidisciplinary approach to ensure the sustainability and effectiveness of smart transportation systems.